Gender Comparisons of Asset and Debt Portfolios in Australia - Austen, Siobhan; Jefferson, Therese; Ong, Rachel (Economic Society of Australia, 2010)
This paper aims to address the gap in the evidence on gender differences in asset and debt holdings by comparing the level of net worth of single women and single men in Australia, and their asset portfolio composition. The findings reveal important gender differences in the level of net worth, especially at the top end of the wealth distribution. Using quantile regression models, we identify that the “route” to high net worth by single women is typically a longer one than it is for single men – in that single women with high net worth are, on average, older than their male counterparts – and the achievement of high net worth by single women is much more heavily dependent on inheritance through widowhood than it is for single men.These findings carry the important implication that there are important gender differences in the ability to independently achieve high levels of wealth in Australia, and single women’s ability to achieve comparable levels of wealth to their male counterparts at each life stage is limited. Furthermore, our findings on asset portfolio composition reveal that single women’s asset portfolios tend to be less diversified than single men; asset portfolios are least diversified among single women aged 65 years or over, reflecting the concentration of wealth held in the primary home among these households.